Group portrait of the attendees of the 84th Annual Session of the California State Grange - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the 84th annual session of the California State Grange, held October 15-19, 1956 at the Municipal Auditorium in Long Beach, California. The attendees are assembled out of doors, in front of a building decorated with a large banner that reads: "84th Annual Session Welcome California State Grange October 15-19"